CONVERSION COATING ON ZINC USING MOLYBDATE ANIONS - Білоусова, Ніна; Фроленкова, Світлана; Ткаченко, Олена; Бик, Михайло (SWorldJournal, 2025)
The paper considers the formation of conversion coatings on zinc in the presence of ammonium molybdate at concentrations of 0.2–2.0 g/dm3 in a solution of weakly mineralized water at room temperature and neutral pH. The electrochemical kinetics of partial